2022
DOI: 10.3390/jof8101059
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Bidirectional Promoter from Trichoderma reesei and Its Application in Dual Gene Expression

Abstract: The cellulolytic filamentous fungus Trichoderma reesei has a strong capability in protein synthesis and secretion and is increasingly used as a fungal chassis for the production of heterologous proteins or secondary metabolites. However, bidirectional promoters that would significantly facilitate multiple genes’ expression have not been characterized in T. reesei. Herein, we show that a 767-bp intergenic region between two polyketide synthase encoding genes that were involved in the biosynthesis of the typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“… 11 The CpG islands were examined using two different approaches. The first approach involves the use of EMBOSS Cpgplot (https://www.ebi.ac.uk/Tools/seqstats/emboss_cpgplot/, Softberry CpG Finder (http://www.softberry.com/berry.phtml?topic=cpgfinder%26group=programs%26subgroup=promoter), and MethPrimer (https://www.urogene.org/methprimer/), with search parameters set according to the Gardiner−Garden and Frommer Algorithm (minimal length of CpG island 200 bp, minimal percentage of G + C 50%, minimal average observed to expected ratio of C + G 0.60) and Takai and Jones Algorithm (minimal length of CpG island 500 bp, minimal percentage of G + C 55%, minimal average observed to expected ratio of C + G 0.65) 12–16 . The second approach entails the use of CLC Genomics Workbench 22.0.2 (http://www.qiagenbioinformatics.com; QIAGEN).…”
Section: Methodsmentioning
confidence: 99%
“… 11 The CpG islands were examined using two different approaches. The first approach involves the use of EMBOSS Cpgplot (https://www.ebi.ac.uk/Tools/seqstats/emboss_cpgplot/, Softberry CpG Finder (http://www.softberry.com/berry.phtml?topic=cpgfinder%26group=programs%26subgroup=promoter), and MethPrimer (https://www.urogene.org/methprimer/), with search parameters set according to the Gardiner−Garden and Frommer Algorithm (minimal length of CpG island 200 bp, minimal percentage of G + C 50%, minimal average observed to expected ratio of C + G 0.60) and Takai and Jones Algorithm (minimal length of CpG island 500 bp, minimal percentage of G + C 55%, minimal average observed to expected ratio of C + G 0.65) 12–16 . The second approach entails the use of CLC Genomics Workbench 22.0.2 (http://www.qiagenbioinformatics.com; QIAGEN).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, natural BDPs have been found in filamentous fungi. It has been shown that BDPs are always intergenic regions regulating the flanking two genes that encode proteins relevant to the same biological process [ 270 ]. The histone H4.1 and H3 promoters can act as natural BDPs, allowing simultaneous expression of enzyme encoding genes in the case of metabolic engineering of Aspergillus sp.…”
Section: Recombinant Dna Strategiesmentioning
confidence: 99%
“…This region was shown to be able to drive the simultaneous expression of two fluorescence reporter genes when fused to each end. This promoter enabled T. reesei to produce cellulases on glucose and improved the total cellulase activities with cellulose Avicel as the sole carbon source [ 270 ].…”
Section: Recombinant Dna Strategiesmentioning
confidence: 99%
“…They typically regulate the transcription of gene pairs that have the same function or participate in the same metabolic process. [ 26 ] Fungi naturally possess bidirectional promoters, such as the pcbAB ‐ pcbC promoters located on the CPC synthesis gene cluster in A. chrysogenum , [ 27 ] two polyketide synthase promoters essential for yellow pigment production in T. reesei , [ 28 ] and two promoters of arabinoxylan degradation enzyme in Fusarium oxysporum . [ 29 ] However, it is notable that current studies are primarily focused on identifying the functions and activities of individual bidirectional promoters, and studies on the establishment of a bidirectional promoter library for filamentous fungi have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%